Osteosarcoma in the femur of a horse. (23rd January 2021) - Pfeifle, R. L.; Beasley, E. M.; Crabtree, N. E.; Fraser, C.; Elbert, J. A.; Ducker, E.; Nagata, K.; Garner, B. C.; Sakamoto, K.
Summary: A 27‐year‐old Arabian pony gelding presented for evaluation of weight loss, intermittent sheath oedema, persistent neutropenia and thrombocytopenia, and acute left hindlimb swelling and gait abnormality. Clinical findings included swelling, heat and sensitivity localised over the left greater trochanter, mild to moderate ventral and sheath oedema, a left hindlimb post‐legged gait, and off‐loading of weight from the left hindlimb at rest. Initially, neutropenia and thrombocytopenia were confirmed on bloodwork, but neutrophilia and thrombocytopenia persisted as the case progressed. Diagnostic imaging (radiography and percutaneous ultrasonography) of the left hindquarters revealed an aggressive, mixed proliferative and lytic bony lesion of the proximal left femur as well as associated muscle fibre disruption and a soft tissue mass. A percutaneous core biopsy of the lesion led to the diagnosis of osteoblastic osteosarcoma on histopathology. Pain and inflammation associated with the lesion was medically managed in the hospital with mild improvement. Additionally, palliative radiation was performed under general anaesthesia. Unfortunately, before a response to palliative radiation could be assessed, the patient was subjected to euthanasia due to development of acute neurological signs.